Why was Leonhard Euler blind?. Issue 1 (2nd January 2022) - Bullock, John D; Warwar, Ronald E; Hawley, H Bradford
Abstract : Leonhard Euler was one of the most eminent mathematicians of all time. In 1735, he developed right periocular swelling, partial loss of vision, and the onset of lifelong recurrent fevers from a heretofore-unknown affliction. Three years later, he developed an infection in the right eye area resulting in right eye blindness, a drooping right upper eyelid with a smaller right pupil, and a right vertical eye muscle imbalance. In 1771, complications from a left cataract operation rendered him almost totally blind now in both eyes. On 18 September 1783, Euler lost the remaining vision in his left eye, and later that day died suddenly from a presumed brain haemorrhage. For centuries, an essential part of the Russian diet had been raw milk, the consumption of which is a significant risk factor for brucellosis (undulant fever) which was endemic in Russia in the eighteenth century (and still is today). Given the history of an acute recurrent infectious febrile illness with ophthalmic and neurological complications and having the probable terminal event being a haemorrhagic stroke, Euler's most likely posthumous diagnoses are ocular, systemic, and neuro-brucellosis with a cerebral haemorrhage from a ruptured Brucella -infected aneurysm.